Homogenization Experiments of Crystal-Rich Inclusions in Spodumene from Jiajika Lithium Deposit, China, under Elevated External Pressures in a Hydrothermal Diamond-Anvil Cell - Jiankang Li; I-Ming Chou (Geofluids)
Extensive studies of the crystal-rich inclusions (CIs) hosted in minerals in pegmatite have resulted in substantially different models for the formation mechanism of the pegmatite. In order to evaluate these previously proposed formation mechanisms, the total homogenization processes of CIs hosted in spodumene from the Jiajika pegmatite deposit in Sichuan, China, were observed in situ under external H2O pressures in a new type of hydrothermal diamond-anvil cell (HDAC). The CIs in a spodumene chip were loaded in the sample chamber of HDAC with water, such that the CIs were under preset external H2O pressures during heating to avoid possible decrepitation. Our in situ observations showed that the crystals within the CIs were dissolved in carbonic-rich aqueous fluid during heating and that cristobalite was usually the first mineral being dissolved, followed by zabuyelite and silicate minerals until their total dissolution at temperatures between 500 and 720°C. These observations indicated that the minerals within the CIs were daughter minerals crystallized from an entrapped carbonate- and silica-rich aqueous solution and therefore provided useful information for evaluating the formation models of granitic pegmatites.